ETC L2 Fluxnet (half-hourly) from Abisko-Stordalen Palsa Bog, 2021-12-31–2025-12-31 - Erik Lundin; Patrick Crill; Håkan Grudd; Jonas Gustafsson; Jutta Holst; Annika Kristoffersson; Alexander Meire; Meelis Molder; Niklas Rakos (Integrated Carbon Observation System, 2026)
Half-hourly Fluxes and Meteo measurements processed with the standard FLUXNET procedure used for the FLUXNET2015 collection (ONEFlux suite).
Lundin, E., Crill, P., Grudd, H., Gustafsson, J., Holst, J., Kristoffersson, A., Meire, A., Molder, M., Rakos, N. (2026). ETC L2 Fluxnet (half-hourly) from Abisko-Stordalen Palsa Bog, 2021-12-31–2025-12-31, ICOS RI, https://hdl.handle.net/11676/DSuguU3bCcTMrux5RCGZbwfb
Keywords: Ecosystem Thematic Centre; ICOS; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; quality flag (int); quality flag (int); incoming shortwave radiation; incoming shortwave radiation; incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; quality flag; quality flag; vapour pressure deficit; vapour pressure deficit; atmospheric pressure; atmospheric pressure; precipitation (total); precipitation (total); wind speed; wind speed; latent heat flux; latent heat flux; sensible heat flux; sensible heat flux; net ecosystem exchange; net ecosystem exchange; ecosystem respiration; ecosystem respiration; gross primary CO2 production; gross primary CO2 production; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap